Role Theory Perspectives: Past, Present, and Future Applications of Role Theories in Management Research - Anglin, Aaron H.; Kincaid, Paula A.; Short, Jeremy C.; Allen, David G. (Journal of management, 2022)
Role theories examine how individual behavior is shaped by prevailing social roles and provide insights into how behavior is perceived by others in light of such roles. Current movements for police reform as well as the landmark decision by the U.S. Supreme Court concerning the employment rights of LGBTQIA individuals have brought conversations concerning roles and their potential impact to the forefront of public discourse. Academic perspectives in management research have aided in building knowledge concerning how roles impact individuals and organizations in a variety of research domains, including entrepreneurship, human resource management, organizational behavior, and strategic management. While the utilization of role theory has gained tremendous momentum over the past two decades, its central tenets are often blurred given that several related but unique perspectives surrounding roles exist in the literature. We trace the origins and development of specific role theories by defining central constructs to bring clarity to the conceptual ambiguities between various role theories and key concepts. Next, we provide an integrative review of empirical role research in management journals over the past 20 years. Here, we identify the five most prominent research themes in the management literature: roles and identity, work–nonwork interface, biases and stereotypes, career life cycles, and ethics and other-oriented behavior. Finally, we provide an agenda for future research that highlights missed opportunities in management research that draws from the key themes identified in our review.